Why is Lake Urmia Drying up? Prognostic Modeling With Land-Use Data and Artificial Neural Network - Rahimi, Akbar; Breuste, Jürgen (Frontiers in Environmental Science, 2021)
Lake Urmia (LU) is considered as the largest salt water lake in Iran and has severe restrictions on water resources and becoming a salt lake increasingly. Using satellite imagery, we evaluated the present situation and changes of the lake area in the past and further changes until 2025. The results indicated that from 1987 to 2000, the process of change has slowed down and less than 2% of the lake's water area was reduced, and from 2000 to 2010, these shrinking processes were faster and more than 28% of the lake water area disappeared. The intensity of the shrinking from 2010 to 2014 is very severe. Using the Land Transformation Model, the continuation of the changes was modeled until 2025. The results of the modeling indicate the conversion of the water lake to salt lake in this period, and in the north part the shallow waters actually occupy 0.7% of the total lake area. The result shows that the climate changes were not the significant factors for drying up of the lake, but human factors such as dams to store water for irrigation, increasing groundwater use by established deeper wells for agricultural irrigation were the important factors for drying. With changing of management of the waters leading to the lake and the transfer of new water resources to the lake between 2014 and 2016, the area of the lake increased to a double. It was visible that by proper planning and managing of water resources the lake's restoration can be achieved.